Kerajaan Turki Usmani: Kajian Keberlangsungan Peradaban Islam Di Eropa: Penelitian - Desi Chayani Wulan; Edi Yusrianto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The Ottoman Empire played a highly crucial role, especially in the expansion of Islamic territories and the development of Islamic civilization in Europe. The peak of Ottoman advancement occurred under the leadership of Sultan Suleiman I. He was known as al-Qanuni, meaning “the lawgiver,” because he successfully formulated laws to regulate society. During the Islamic golden age, many Europeans came to learn and seek knowledge from Muslims, enabling them to emerge from the Dark Ages. The Islamic world had once reached great heights in science, technology, and philosophy, particularly under the Abbasid Dynasty, which lasted from the 8th to the 15th century. This study uses library research with a historical approach. The results show that the Ottoman Empire achieved significant glory in its era, successfully expanding Islamic territories across three continents and managing the longest-lasting government in Islamic history (approximately seven centuries) involving 39 ruling leaders. However, the Ottoman government placed strong emphasis on military strength; the kingdom’s position would weaken if its military institutions were not well maintained, while a strong military contributed to the empire’s progress. Nevertheless, the military still played an important role in supporting the greatness of the Ottomans.